Tacrolimus and Azole Derivatives of Agricultural and Human Health Importance: Prediction of ADME Properties - Antypenko, Lyudmyla; Shabelnyk, Konstyantyn; Kovalenko, Sergiy (Current Computer - Aided Drug Design, 2024)
Introduction Agricultural chemicals are impacting health nowadays. Recently, promising synergistic antifungal interaction between tacrolimus and some azole compounds was studied. Objective To determine ADME parameters, potential side effects of test substances to reduce time and resources in the future. Methods All descriptors and molecular parameters were obtained by the protocols ofSwissADME and ProTox II. Results In the result, the following physicochemical and drug-likeness parameters were calculated. Conclusion Studied triazoles 1 and 2 showed good ADME characteristics and promising toxicity levels suitable to be checked for in vitro toxicology in case of future advanced results in theagricultural field.
Keywords: hymexazol